Rudiments of External Audit in Interwar Lithuania - Lakis, Vaclovas (Ekonomika, 2007)
When the Lithuanian State was established in 1918, institutions of external audit began to form. The main audit institutions were State Control and Inspectorate of Publicly Accountable Firms and Institutions. January 16, 1919 can be considered the date of establishment of the institution of State Control in Lithuania. Then a temporary State Controller was appointed. In the beginning, there was no law to regulate the activity of the State Control, therefore conflicts between the State Control and the auditees, especially the Government regarding auditing procedures and realization of their results, were common. The Law on the State Control was adopted at the end of February 1919. It provided that the State Control was supposed to perform the check of the state’s assets, finances, the correctness and legality of its operations. Subjects to audit by the State Control were all State institutions and municipalities, institutions that received financial support from the State and companies that took advantage of the credits and guarantees of the State. The auditees were supposed to provide the State Control arth all the working papers reflecting their activities. The State Control initiated and carried out auditing procedures at its discretion. The independence of the State Control was reinforced by the Temporary Constitution in which the status and activities of the State Control were defined clearly and at length. There were two kinds of audit: documentary and factual. During a documentary audit, papers were verified, and during a factual audit, physical verification and field audit were performed. The Inspectorate of Publicly Accountable Firms and Institutions audited credit and insurance institutions, exchanges, industrial companies and other companies and institutions that had to account in public. The above mentioned institutions analysed: 1) whether the auditees’ activities conformed to laws and other statutory acts; 2) whether account books were in order; 3) whether credits received from the State’s budget were properly used. The activity of the Inspectorate was constantly criticized and law amendment projects were announced. State Control and the Inspectorate of Publicly Accountable Firms and Institutions existed till Lithuania became annexed by the Soviet Union. The major reforms began in July 1940 when the Inspectorate of Publicly Accountable Firms and Institutions was merged with State Control and, one month later. reorganized into the People’s Commissariat of State Control (people’s commissariat then stood for a ministry). Together with audit, the commissariat began to perform political and governmental functions. Employees of the commissariat participated in the nationalization of companies and institutions. The main institutions of the present external audit are the National Audit Office and independent auditing companies. The National Audit Office carries out the audit of: 1) state budget implementation and use of State funds; 2) management, use and disposal of State property; 3) implementation of the budget of the State Social Insurance Fund and the Compulsory Health Insurance Fund; 4) the use of funds of the European Union allocated to the Republic of Lithuania. The National Audit Office submits to the Seimas conclusions on the account of the execution of the State budget, on the Government report on public debt, and on State property. Independent audit companies can carry out audit, perform various checks, analyses, inventories, provide bookkeeping services, counsel on bookkeeping and taxes perform an expert examination of accounting and accountability in name of the court, evaluate the conditions of companies’ reorganization, perform internal audit. The main goals of the activity of State Control in the interwar and present day Lithuania have not changed and are checking the management and use of State property and finances. In the interwar period inspection was performed, and today financial and performance audit are executed. In both cases, legality and rationality are the subjects of inspection. Nowadays, the focus is rather on the effectiveness of the use of property and funds and the correctness of financial accountability. However. these issues were not overlooked in interwar Lithuania, either. Therefore, it is true to say that National Audit was formed in interwar Lithuania.